The role of realia in Khaled Hosseini’s novel “Kiter Runner” - Valiyeva , Nargizaxon (The Lingua Spectrum, 2025)
This article is devoted to the linguocultural analysis of realia presented in Khaled Hosseini's novel «Kite Runner». The primary focus is on the study of ethnographic, geographical, and socio-political realia, their role in the artistic text, and their influence on the perception of national and cultural specificity. Using the classification proposed by D.U. Ashurova and M.R. Galieva, the author systematized the realia presented in the novel and identified their functions: background, identificational, cultural-informative, communicative, and illustrative. Particular attention is given to anthroponyms, toponyms, names of national dishes, clothing, holidays, and religious directions, which create an authentic depiction of Afghan culture. The analysis confirmed that realia perform not only aesthetic and descriptive functions but also serve as a powerful tool for immersing the reader in the cultural and ethnographic space. Their use contributes to a deeper understanding of the Afghan people’s mentality and serves as an essential tool for intercultural communication, helping to overcome linguistic and cultural barriers. The findings of this study emphasize the significance of realia as a means of intercultural communication, enabling a deeper appreciation of the cultural heritage and mentality of the described nation.